Synthesizing runtime programmable switch updates - Qiu, Yiming; Beckett, Ryan; Chen, Ang (Network System Design and Implementation, 2023)
We have witnessed a rapid growth of programmable switch applications, ranging from monitoring to security and offloading. Meanwhile, to safeguard the diverse network behaviors, researchers have developed formal verification techniques for high assurance. As a recent advance, network devices have become runtime programmable, supporting live program changes via partial reconfiguration. However, computing a runtime update plan that provides safety guarantees is a challenging task. FlexPlan is a tool that identifies step-by-step runtime update plans using program synthesis, guaranteeing that each transition state is correct with regard to a user specification and feasible within switch memory constraints. It develops novel, domain-specific techniques for this task, which scale to large, real-world programs with sizable changes.